Adaptive Finite-Time Attitude Tracking of Quadrotors With Experiments and Comparisons - Tian, Bailing; Cui, Jie; Lu, Hanchen; Zuo, Zongyu; Zong, Qun (IEEE transactions on industrial electronics (1982), 2019)
The finite-time attitude control of quadrotor unmanned aerial vehicles (UAVs) subject to external disturbances with unknown bound is investigated in this paper. First, an adaptive multivariable finite-time stabilizing control algorithm for second-order multivariable systems is developed based on the improved supertwisting and the equivalent control algorithms. Furthermore, the finite-time stability conditions are derived via the Lyapunov technique. The remarkable feature of the developed algorithm is to eliminate the overestimation of the control gains without loss of the sliding motion. Then, the proposed algorithm is applied for quadrotor UAVs to solve the finite-time attitude-tracking problem. Finally, a comparison of the proposed multivariable algorithm with its scalar counterpart is presented and validated both by simulation and experiment results.